2009
DOI: 10.1002/mrd.21126
|View full text |Cite
|
Sign up to set email alerts
|

Nucleoli from growing oocytes support the development of enucleolated full‐grown oocytes in the pig

Abstract: Recent research has shown that the maternal nucleolus is essential for embryonic development. The morphology of the nucleolus in growing oocytes differs from that in full-grown oocytes. We determined the ability of nucleoli from growing oocytes to substitute for nucleoli of full-grown oocytes in terms of supporting embryonic development in this study. Growing (around 100 microm in diameter) and full-grown porcine oocytes (120 microm) were collected from small (0.6-1.0 mm) and large antral follicles (4-5 mm), r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 27 publications
0
13
0
Order By: Relevance
“…The nucleoli of growing pig oocytes, which were treated with actinomycin D, supported embryonic development to a similar extent as nucleoli collected from full‐grown oocytes (Kyogoku et al, 2010). This report also showed that it was possible to collect growing oocyte nucleoli, when the oocytes were treated with actinomycin D. Using this enucleolation method, we examined the effect of growing oocyte nucleoli on oocyte maturation.…”
Section: Discussionmentioning
confidence: 67%
See 2 more Smart Citations
“…The nucleoli of growing pig oocytes, which were treated with actinomycin D, supported embryonic development to a similar extent as nucleoli collected from full‐grown oocytes (Kyogoku et al, 2010). This report also showed that it was possible to collect growing oocyte nucleoli, when the oocytes were treated with actinomycin D. Using this enucleolation method, we examined the effect of growing oocyte nucleoli on oocyte maturation.…”
Section: Discussionmentioning
confidence: 67%
“…Oocytes were enucleolated as described previously (Kyogoku et al, 2010). Briefly, full‐grown and growing oocytes were transferred into HEPES‐199 containing 12.5 µg/ml cytochalasin B and 0.01 µg/ml demecolcine for 10 min.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…This acquisition of full meiotic competence coincides with the morphological change in the nucleolus. In the present experiment, growing pig oocytes collected from 0.6 to 1.0 mm follicles were around 100 µm in diameter (Kyogoku et al, 2010). Oocytes of this size do not have the ability to complete the maturation (Kanayama et al, 2002).…”
Section: Discussionmentioning
confidence: 75%
“…In the GV, the oocyte chromatin again enclosed the reassembled nucleolus. Nucleoli are formed in pronuclei of activated, enucleolated‐matured oocytes after their re‐injection at the MII stage (Ogushi et al, 2008; Kyogoku et al, 2010). Since the oocyte nucleoli disappear during oocyte maturation and reappear in the pronucleus of zygotes, it is logical that injected nucleoli disappear in the oocyte cytoplasm at the MII stage.…”
Section: Discussionmentioning
confidence: 99%